Two Novel Mutations in the SI Gene Associated With Congenital Sucrase-Isomaltase Deficiency: A Case Report in China - Zhou, Jianli; Zhao, Yuzhen; Qian, Xia; Cheng, Yongwei; Cai, Huabo; Chen, Moxian; Zhou, Shaoming (Frontiers in Pediatrics, 2021)
Background: Congenital sucrase-isomaltase deficiency (CSID) is an autosomal recessive inherited disease in nature and leads to the maldigestion of disaccharides and is associated with the mutation of the sucrase-isomaltase (SI) gene. Cases of CSID are not very prevalent in China or around the world but are gradually being identified and reported. Case presentation: We report the case of a 14-month-old male who was failure to thrive that began after food diversification and admitted for chronic diarrhoea. We used whole exome sequencing (WES) approach to identify the mutations in this patient’s genome, that showed two novel heterozygous mutations in the SI gene, c.2626C>T (p. Q876*) and c.2872C>T (p. R958C), and were further confirmed by DNA Sanger sequencing. With a strict sucrose- and starch-restricted diet, this patient’s diarrhoea stopped and he began to gain weight. Conclusions: We report a case of novel variants in the SI gene that caused CSID, which provides valuable experience for the clinical field, especially in China.